Marketing in the food trade - Ewa Bąk-Filipek; Urszula Tetwejer (Polityki Europejskie, Finanse i Marketing)
The marketing of food products on the mark et especially large role is played by trade. Direct contact with the ultimate consumer, trade, gives a chance for widespread use of marketing methods. The methods and marketing strategies resulting from the sale of forms and types of units in retail and wholesale. This paper reviews the various combinations of the sale of food products, offering various opportunities for marketing activities. Retail trade, in which consumers are stocking up on food, is very developed, yet extremely diverse. There are many companies and organizations engaged in the retail sale of food and new ones are emerging. In the event of major importance to food self-service sales, and sales of traditional, full service provider of customer and dealer support. The food trade the most important are two groups of shops, i.e. shops 35 specialized and general food stores, offering a wide range of goods. Although sales dominated the market for grocery storefront, there is also developed outside the storefront sale. In highly developed countries rapidly develop modern forms of selling food products, resulting in overall sales growth outside the storefront. In the case of food it can include the following forms of sales: market sales and bazaars, sales of agricultural food products manufacturers in their farms, and otherwise than by itinerant sales (doorstep), mail-order sale of vending machines, sale of home delivery, etc. Sales of food products directly on farms plays a greater role, among others due to the desire of consumers to buy food from a known source and the rise of the so-called. healthy food. Not without significance for this form of supply is to increase the vividness of the number of cars owned by individuals, which facilitates communication and transport.